2016
DOI: 10.2298/ciceq141125012z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and synergistic effects of co-pyrolysis of yinning coal and poplar sawdust

Abstract: Co-process of biomass and coal is perceived as a way to enhance the energy utilization by virtue of the integrated and interactive effects between different types of carbonaceous fuels. The purpose of this study was to investigate the co-pyrolysis characteristics of Yining coal and poplar sawdust, and to determine whether there is any synergistic effect in pyrolytic product yields. The coal was blended with sawdust at a mass fraction of 9:1, 7:3, 5:5, 3:7 and 1:9 respectively. The change of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several authors have investigated the combined pyrolysis of coal and biomass, highlighting its significance. Zhu et al investigated the synergies of co-pyrolysis of Yining coal and poplar sawdust at different blending ratios. They concluded that coal/biomass blends produces less char and tar than if they underwent pyrolysis separately.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have investigated the combined pyrolysis of coal and biomass, highlighting its significance. Zhu et al investigated the synergies of co-pyrolysis of Yining coal and poplar sawdust at different blending ratios. They concluded that coal/biomass blends produces less char and tar than if they underwent pyrolysis separately.…”
Section: Introductionmentioning
confidence: 99%